SuFLexQA: an approach to Question Answering from the lexicon - Cardellino, Cristian (2013)
We present SuFLexQA, a system for Question Answering that integrates deep linguistic information from verbal lexica into Quepy, a generic framework for translating natural language questions into a query language. We are participating in the QALD-3 contest to assess the main achievements and shortcomings of the system.